Assessment of predictive risk factors in difficult laparoscopic cholecystectomy: A single center study from central India - Jagne, Nilesh; Ansari, Shagufta Naaz; Chauhan, Mahendra; Goyal, Pankaj; Rahangdale, Sachin; Rathod, Rahul (Asian Journal of Medical Sciences, 2025)
Background: Laparoscopic cholecystectomy (LC) has become the most common procedure for the management of symptomatic cholelithiasis. Based on the difficulty faced during the procedure the outcome of LC could vary from partial cholecystectomy to conversion into open cholecystectomy. Thus, for surgeons, it would be important to assess predictive factors and conversion preoperatively. Aims and Objectives: The objective of the present study was to assess various demographic, pre-operative, and intra-operative factors of difficult LC. Materials and Methods: The present study is a hospital-based observational study. A total of 119 patients having symptomatic cholelithiasis who underwent elective LC were included in the present study. Results: It was found that among all the pre-operative factors gallbladder (GB) wall thickness, obesity, and impacted stones in Hartmann’s pouch were found to be significantly associated with difficult LC. Furthermore, among the intra-operative factors GB adhesion, omental adhesions, gall extraction, duct, and clipping were found to be significantly associated with difficult LC. Conclusion: The present study recommends that both pre-operative and intra-operative factors should be regularly used as a protocol for the prediction of difficult LC. With a little extra attention, the procedure-related complications could be further reduced to an acceptable level in LC.